In vivo Analgesic activity of methanolic extract of Helianthus annuus seeds - Islam, Rubab Tarannum; Islam, Ahmed Tanjimul; Hossain, Mir Monir; Mazumder, Kishor (International Current Pharmaceutical Journal, 2016)
The sunflower seed is the seed of the sunflower (Helianthus annuus). The methanol extract of seeds of Helianthus annuus were screened for analgesic activity in mice model to systematically explore the medicinal values of the plant. Acetic acid induced writhing and hot plate methods were used to confirm the central and peripheral analgesic action. In case of acetic acid-induced writhing test the extract showed significant (P <0.05) analgesic potential at doses 100 and 200 mg/kg body weight (50.35 and 57.85% inhibition, respectively). In the hot plate method, increase (p < 0.05) of latency period was also observed in comparison to standard aspirin. At 60 minutes, the latency period of two different doses (100 and 200 mg/kg body weight) was found at 13 ± 0.91 and 16.5 ± 1.55 second. The results obtained support the use of Helianthus annuus seeds in painful conditions acting both centrally and peripherally. Islam et al., International Current Pharmaceutical Journal, March 2016, 5(4): 38-40 http://www.icpjonline.com/documents/Vol5Issue4/02.pdf